SISTEM PENGUPAHAN DALAM PERSPEKTIF HUKUM ISLAM - Safwan; Benazir (Jurnal Tahqiqa : Jurnal Pemikiran Hukum Islam, 2023)
This research was conducted to determine the wage system in the perspective of Islamic law, with data collection techniques using observation and documentation methods. Data analysis in this study will use qualitative data analysis which is constructive, develops and discovers social theories. The results obtained from this study are that the wage payment system must be in accordance with the agreement, so that wage earners can overcome some of the economic difficulties that are needed daily. The act of delaying the payment of wages without a valid reason is very contrary to Islamic law and is classified as an unjust act, what is more important in the matter of wages is that before working as a girlfriend, both parties first inform or provide an explanation regarding the amount of wages that must be received or arrested. so that there is no interpretation at a later date. Islam also explains that in the wage payment system, the wages that workers will receive